Organic and non-organic semiconductor materials for pulsed fiber laser generation in 1.55-micron region / Farina Saffa Mohamad Samsamnun - Farina Saffa , Mohamad Samsamnun (2021)
This thesis demonstrated several types of Erbium-doped fiber lasers (EDFLs) based on newly developed organic and inorganic semiconductor material as saturable absorbers (SAs). Six new materials; Gallium nitride (GaN), Silicon (Si), Poly (3-hexylthiophene-2,5-diyl) Regioregular (P3HT), Tris (8-hydroxyquinolinato) Aluminium (Alq3), Poly [2- methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV) and Poly (9- vinylcarbazole) (PVK) were successfully explored to generate Q-switched and modelocked pulses operating at 1.55-micron region. For instance, by slotting in the prepared Alq3 thin film in between two fiber ferrules in the EDFL cavity, Q-switched laser operating at 1560 nm was obtained with the highest pulse energy of 73.21 nJ. As the pump power was increased from 45 mW to 98 mW, the repetition rate of the Q-switched EDFL increased from 70.42 kHz to 91.24 kHz while the pulse width reduced from 4.48 μs to 3.26 μs. By inserting an additional SMF into the laser cavity to tailor the dispersion characteristic and nonlinearity, the mode-locked pulses were successfully generated with these SAs. For instance, a stable soliton mode-locked fiber laser was also realized by adding 100 m long SMF in the EDFL cavity configured with PVK SA. At the maximum pump power of 187 mW, the laser generated a pulse train with a repetition rate of 1.866 MHz, pulse energy of 2.00 nJ, pulse width of 2.81 ps and output power of 3.75 mW. The mode-locked laser had a high SNR of 63.10 dB, which indicates an excellent stability of the pulses. However, the P3HT based mode-locked laser produced the shortest pulse width of 2.62 ps. This work introduces a new application of organic and inorganic semiconductor material to nonlinear photonics, emphasizing the application of these materials in Q-switched and mode-locked fiber lasers.